Effectiveness of an integrated 4T intervention test, treat, talk and track in mitigating anemia among tribal communities in Telangana, India - Gupta, Vikram; Neeladdi, Nehana; Mantha, Venkat Rao; Gop, Bhagirath; Chittapur, Dhanaraj (International Journal Of Community Medicine And Public Health, 2026)
Background: Anaemia affects over 1.6 billion people worldwide, with India bearing a disproportionate burden despite five decades of national programming. Telangana’s 70% prevalence exceeds the 67.1% national average, with tribal districts like Bhadradri Kothagudem suffering from poor dietary diversity, limited healthcare access, and socioeconomic disadvantages. This study evaluated whether an integrated "4T" intervention- Test, Treat, Talk, and Track - could reduce Anaemia in this vulnerable population. Methods: A community-based longitudinal study was conducted in Laxmidevipally Mandal, Bhadradri Kothagudem, covering 1,228 households across 16 villages with a baseline population of 5,291. Haemoglobin levels were screened using the non-invasive EzeCheck device. Anaemic participants received targeted medical treatment, Behaviour Change Communication (BCC), and Nutri-kits for home kitchen gardens. Results: Following quarterly follow-ups and matched endline analysis, overall anaemia prevalence dropped significantly from 64.59% to 53.75% (p<0.001), representing a 10.84 percentage point reduction, with the largest reduction occurring among adolescent girls. Severe anaemia fell by 63% (from 9.8% to 3.6%), and mean haemoglobin levels rose from 11.0 to 11.6 g/dl. Among baseline severe cases, 24.4% recovered to normal or mild status, though 51.7% of the total cohort remained persistently anaemic. Furthermore, a notable knowledge-practice gap remained, while 96% of participants recognized green leafy vegetables as essential, only 56% had consumed them in the past 24 hours. Conclusions: The 4T model successfully yielded measurable health gains. However, high residual Anaemia and behavioural gaps underscore the need for extended, region-specific interventions, consistent Iron Folic Acid (IFA) supply chains, and sustained community communication.